Pendidikan dan Proses Pembudayaan dalam Keluarga - Suharyanto, Agung (Universitas Negeri Medan, 2015)
Enculturation process is done by parents, or the person considered as senior by children or by the younger. Manners, customs, skill of a tribes/family usually inherited to the next generation through enculturation. In the family, in the first time children have early direct experiences which will be used as provision of their life later by physical exercise, social, mental, emotional even spiritual.